Interviewing Peter Lang - Markou, Smaro (Murmurations: Journal of Transformative Systemic Practice, 2022)
This interview took place 15 years ago on 26th January, 2007 when Peter Lang was visiting Smaro Markou’s centre in Athens. It was originally published in Metalogos, The Greek Systemic Therapy Journal and we thank Fany Triantafillou and team for their generosity in allowing us to re-produce it here. The interview has a new introduction and conclusion by Smaro Markou in which she offers some context and recent reflections on this meeting and on Peter’s contribution to the systemic field.